Leaving Readers and Writers in Peace: Translation of Religious Terms of Shakespeare’s "Coriolanus" into Arabic considering Venuti’s Invisibility - Mizher, Rabab (Multicultural Shakespeare: Translation, Appropriation and Performance, 2020)
This paper is an endeavour to examine the translation of religious terms (praying and oath words) in Shakespeare’s Coriolanus pertaining to two translations by Muhammad al-Sibā‘ī (1881-1931) and Jabra Ibrahim Jabra (1920-1994) into Arabic. This paper seeks to ascertain whether the translators opt for leaving readers in peace and bringing source text (ST) writers’ home or leaving writers in peace and sending target text (TT) readers abroad. The study is based on the theoretical framework of Descriptive Translation Studies (DTS) and the pivotal role the translated literature as facts of the target culture in the poly-system of world literature. The study reveals that each of these translations represents a specific strategy in translation. Visible translator is mostly adopted by Jabra Ibrahim Jabra and invisible translator is mostly adopted by Muhammad al-Sibā‘ī.